(untitled) (Research, Society and Development, 2020)
Since the beginning of the year 2020, Brazil and the world have faced a health crisis arising from the emergence and spread of COVID-19. As an emergency to combat the disease in question, the World Health Organization (WHO) recommended social distancing. However, this measure is notably incompatible with the current educational system. Therefore, it was necessary to search for digital means and technologies of communication and information, in order to guarantee a quality education, as well as greater training of the faculty to deal with the new reality. In this perspective, this work aimed to analyze the challenges in the training of education professionals in times of pandemic, in order to explain how the current conditions of teacher training and its adaptations, as well as the challenges in the school context in view of the distance policy Social. The methodology used was of a descriptive character, through a bibliographic survey, in which were articles, dissertations and theses related to the training of professionals, education and learning, as well as the challenges arising from remote teaching. The study listed the difficulties and challenges facing remote education, these coming from the specific classification for teachers, social awareness, as well as the precarious and lagged access of the school community to technological resources.